Siliceous foam material and its application in post-combustion carbon capture for NGCC plants: effects of aging conditions - Meng, Yang; Yan, Yuxin; Jiang, Peng; Wu, Xinyun; Sun, Cheng-gong; Wu, Tao; Pang, Cheng Heng (EDP Sciences, 2020)
In an effort to reduce the overall energy penalty and capital expenditure associated with carbon capture technologies, a variety of porous solid adsorbents have been developed. The limitations of solid sorbent in large-scale process are related to its CO2 uptake, physicochemical stability, lifecycle, regenerability and operation condition. In this paper, siliceous foam materials were synthesized via a modified microemulsion templating method and functionalized with branched polyethylenimine (PEI). The physical characteristics of synthesized silica adsorbents under different aging conditions were analysed via N2 sorption analysis and Scanned Electron Microscopy (SEM) morphological analysis. CO2 uptake was evaluated by thermogravimetric analyser (TGA). The results show that CO2 uptake is desirable even under low CO2 partial pressure and is predictable with multiple linear regression (MLR) model in the range of examined materials.